Peranan Bahan Organik dalam Peningkatan Produksi Kedelai dan Ubi Kayu pada Lahan Kering Masam - Muzaiyanah, Siti; Subandi, Subandi (Puslitbang Tanaman Pangan, 2016)
Increased production of soybean and cassava can be reached by alternatively extending cultivation to suboptimal land, such as upland acid soil, where amelioration of organic material is an attempt to improve soil fertility. The sources of organic material can be obtained from the agricultural and non-agricultural waste, such as: compost and manure. Organic materials are not only beneficial for improving the chemical, physical, physico-chemical and biological soil characters, but also capable of supporting plant growth to produce higher yields in soybean and cassava.